2022
DOI: 10.1159/000526243
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Patients with Alzheimer’s Disease and a History of Traumatic Brain Injury

Abstract: Introduction Traumatic brain injury (TBI) has been associated with a greater risk of developing Alzheimer's disease (AD). Less is known about the clinical features of AD patients with TBI history. The objective of this study was to examine whether a history of TBI and specific injury characteristics are associated with differences in age of disease onset, cognitive features, and neuropsychiatric symptoms (NPSs) in AD patients. Methods Biomarker-proven AD patients (CSF o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…In other series, the follow-up between TBI and AD was a mean of 7.8 years [19] or up to 18 years after TBI [69]. This and another recent clinical study showing a lower percentage of APOE ε4 genotype in AD patients with a TBI history [70], like ours indicated that closed head injury is a factor in the development of AD among subjects lacking APOE ε4 alleles, whereas experimental studies showed that transgenic mice expressing human APOE ε4 are more susceptible than those express-ing APOE ε3 to closed head injury, probably related to a preventive function of APOE ε3 and an APOE ε4-related pathological function [71]. Thus, the role of the APOE genotype in the development of AD following TBI remains inconclusive and ambiguous [72].…”
Section: Discussionmentioning
confidence: 54%
“…In other series, the follow-up between TBI and AD was a mean of 7.8 years [19] or up to 18 years after TBI [69]. This and another recent clinical study showing a lower percentage of APOE ε4 genotype in AD patients with a TBI history [70], like ours indicated that closed head injury is a factor in the development of AD among subjects lacking APOE ε4 alleles, whereas experimental studies showed that transgenic mice expressing human APOE ε4 are more susceptible than those express-ing APOE ε3 to closed head injury, probably related to a preventive function of APOE ε3 and an APOE ε4-related pathological function [71]. Thus, the role of the APOE genotype in the development of AD following TBI remains inconclusive and ambiguous [72].…”
Section: Discussionmentioning
confidence: 54%